Tinjauan Yuridis Penyelesaian Kredit Macet pada Bank Perkreditan Rakyat Berkah Pakto Kediri, Jawa Timur - Pitono .; Weppy Susetiyo (Universitas Islam Balitar, Blitar, 2019)
One of the efforts of the Rural Bank (BPR) based on Article 13 of the Republic of Indonesia Law Number 10 of 1998 concerning Banking is to provide credit. But in credit matters, especially in the BPR Berkah Pakto, it does not always run smoothly. Bad credit, becoming one type of non-performing loans with the largest amount in this BPR. Through sociological (juridical-empirical) juridical research at BPR Berkah Pakto Kandangan-Kab. Kediri, East Java, the research results are obtained that the factors that cause the occurrence of bad credit in BPR Berkah Pakto consist of factors originating from customers (debtors), factors originating from BPR Berkah Pakto, and other party factors. The process of settling bad debts at the Perkreditan Rakyat Berkah Pakto Bank optimizes non-legal channels to be able to settle its obligations.